THE WORD FORMATION PROCESSES OF TRAVELING TERMS IN “BLACK MEETINGS & TOURISM” MAGAZINE - YULIANA, - (Jurnal Ilmiah Mahasiswa FIB, 2013)
People use language in their daily life to communicate to each others. In communicating, there are two forms of how language can be produced, namely oral and written forms. We can easily know the oral form of language through conversation in daily life. Meanwhile, the written form can be found in either formal or informal one, for example in the magazine, newspaper, novel, etc. Magazine is one way to get information. Like tourism magazine, people get information about place, hotel and many others things about traveling. Most of them offer news in English.The use of English in tourism magazine normally is not easily understood because there are some specific words that the readers do not know before. In this study, the writer is interested in analyzing word formation processes of traveling terms. It is because word formation processes is a way of forming new words or terms from the use of old words (Yule, 1985).This study is aimed to investigate the kind word formation processes of traveling terms and find out the meaning of the words formation processes of traveling terms in “Black Meetings & Tourism” magazine Nov/Dec 2012 edition. The writer uses Yule’s theory (1985)and O’Grady’s theory (1996) to analyze the data. The result of the study is expected to give significance to the next researchers who are interested in studying morphology especially about word formation processes. They are expected to conduct similar studies by using other media such as movie, newspaper and other magazine or maybe by using any other terms such as fashion, sports, etc. Kata Kunci: proses pembentukan kata, istilah-istilah pariwisata majalah.